Review paperChromoblastomycosis - Krzyściak, Paweł M.; Pindycka-Piaszczyńska, Małgorzata; Piaszczyński, Michał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Chromoblastomycosis is a chronic fungal infection of the skin and subcutaneous tissue. The infection usually results from a traumatic injury and inoculation of microorganism from a specific group of dematiaceous fungi (usually Fonsecaea pedrosoi , Phialophora verrucosa , Cladophialophora carrionii ). In the tissues fungi produce characteristic sclerotic cells or muriform cells. Dermal lesions can range from small nodules to large papillary-like eruptions. The disease has been described worldwide but the prevalence is higher in rural populations in countries with a tropical or subtropical climate, such as Madagascar in Africa and Brazil in South America. Diagnostic techniques are based on direct examination, culture and histopathology. Despite a variety of treatment modalities, which include long courses of antifungals, surgical excision and destructive physical therapies, the disease remains one of the most difficult deep mycotic infections to eradicate.